Analisis Kemampuan Mahasiswa Dalam Menyelesaikan Soal Struktur Aljabar II Pada Mahasiswa Semester VI Program Studi Pendidikan Matematika FKIP UMS - Setyaningsih, Riyatin, Dra. Sri Sutarni, M.Pd, Sri Rejeki, M.Pd, M.Sc (2015)
The aim of this study is to know students' ability in solving some problems of Abstract Algebra II. It is observed from the level of remembering, understanding, applying, and analyzing of the students of VI Grade in 2015/2016 academic year of Mathematic Education Department. This study is a descriptive qualitative research. The data were collected by using test, observation, documentation, and interview. The data were analyzed by using qualitative method that is divided into three steps, namely data reduction, data presentation, and drawing conclusion. The result of the study shows that the students' ability solving the problems of Abstract Algebra II in the level of remembering (60,1136 %) within sufficient criteria, understanding (42,1591 %) within sufficient criteria, applying (52,8409 %) within sufficient criteria, and analyzing (35,5682 %) within poor criteria.